Identification, Typing, Antifungal Resistance Profile, and Biofilm Formation of Candida albicans Isolates from Lebanese Hospital Patients. (1st June 2014) - Bitar, Ibrahim; Khalaf, Roy A.; Harastani, Houda; Tokajian, Sima
Abstract : As leading opportunistic fungal pathogens identification and subtyping of Candida species are crucial in recognizing outbreaks of infection, recognizing particularly virulent strains, and detecting the emergence of drug resistant strains. In this study our objective was to compare identification of Candida albicans by the hospitals through the use of conventional versus identification based on the ITS (Internal Transcribed Spacer) and to assess biofilm forming capabilities, drug resistance patterns and correlate these with MLST typing. ITS typing revealed a 21.2% hospital misidentification rate. Multidrug resistance to three drugs out of four tested was detected within 25% of the isolates raising concerns about the followed treatment regimens. Drug resistant strains as well as biofilm formers were phylogenetically related, with some isolates with significant biofilm forming capabilities being correlated to those that were multidrug resistant. Such isolates were grouped closely together in a neighbor-joining tree generated by MLST typing indicating phylogenetic relatedness, microevolution, or recurrent infection. In conclusion, this pilot study gives much needed insight concerning C. albicans isolates circulating in Lebanese hospitals and is the first study of its kind correlating biofilm formation, antifungal resistance, and evolutionary relatedness.